2022
DOI: 10.1039/d2se00610c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of sucrose to 1,2-propanediol over alumina-supported Ni–Mo bimetallic catalysts

Abstract: The metal combination of 8%Ni–20%Mo/γ-Al2O3 is found to be effective in producing a good yield of 1,2-propanediol (∼74%) under mild reaction conditions of 180 °C, 40 bar H2 pressure at a run time of 4.5 h in a batch reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Our previous study reported ∼74% 1,2-PD yield using 8%Ni-20%Mo/γ-Al 2 O 3 under the reaction conditions of 180 °C, 40 bar H 2 pressure, and 4.5 h reaction time. This report reveals that the combination of Ni–Mo and tuned acidity and basicity helps obtain 1,2-PD selectively under milder reaction conditions.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our previous study reported ∼74% 1,2-PD yield using 8%Ni-20%Mo/γ-Al 2 O 3 under the reaction conditions of 180 °C, 40 bar H 2 pressure, and 4.5 h reaction time. This report reveals that the combination of Ni–Mo and tuned acidity and basicity helps obtain 1,2-PD selectively under milder reaction conditions.…”
Section: Introductionmentioning
confidence: 98%
“…19 The main reaction pathway for sucrose hydrogenolysis is depicted in Scheme 1 based on the literature. 17,18 The pathway provided illustrates the reactions in converting sucrose to various products. Initially, sucrose undergoes hydrolysis to produce glucose and fructose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Therefore, replacing water oxidation with a new oxidation reaction to reduce energy consumption and to produce higher value product (than oxygen) is attracting ever-increasing interest. 9,10 Electrooxidation of many different organic molecules has been reported to couple with HER for green H 2 generation, such as biomass, [11][12][13] hydrazine, 14,15 isopropanol, 16 benzylamine, 17 urea, 18 formic acid, 19 and so on.…”
Section: Introductionmentioning
confidence: 99%